Plant, fungal, bacterial, and nitrogen interactions in the litter layer of a native Patagonian forest - Vivanco, Lucía (2018)
Fil: Vivanco, Lucía. Universidad de Buenos Aires. Facultad de Agronomía. Instituto de Investigaciones Fisiológicas y Ecológicas Vinculadas a la Agricultura (IFEVA). Buenos Aires, Argentina.